An Epigenetic Regulator: Methyl-CpG-Binding Domain Protein 1 (MBD1) - Li, Lu (Int J Mol Sci, 2015)
DNA methylation is an important form of epigenetic regulation in both normal development and cancer. Methyl-CpG-binding domain protein 1 (MBD1) is highly related to DNA methylation. Its MBD domain recognizes and binds to methylated CpGs. This binding allows it to trigger methylation of H3K9 and results in transcriptional repression. The CXXC3 domain of MBD1 makes it a unique member of the MBD family due to its affinity to unmethylated DNA. MBD1 acts as an epigenetic regulator via different mechanisms, such as the formation of the MCAF1/MBD1/SETDB1 complex or the MBD1-HDAC3 complex. As methylation status always changes along with carcinogenesis or neurogenesis, MBD1 with its interacting partners, including proteins and non-coding RNAs, participates in normal or pathological processes and functions in different regulatory systems. Because of the important role of MBD1 in epigenetic regulation, it is a good candidate as a therapeutic target for diseases.